Impact of investigations in general practice on timeliness of referral for patients subsequently diagnosed with cancer: analysis of national primary care audit data - Rubin, G P (Br J Cancer, 2015)
BACKGROUND: For patients with symptoms of possible cancer who do not fulfil the criteria for urgent referral, initial investigation in primary care has been advocated in the United Kingdom and supported by additional resources. The consequence of this strategy for the timeliness of diagnosis is unknown. METHODS: We analysed data from the English National Audit of Cancer Diagnosis in Primary Care on patients with lung (1494), colorectal (2111), stomach (246), oesophagus (513), pancreas (327), and ovarian (345) cancer relating to the ordering of investigations by the General Practitioner and their nature. Presenting symptoms were categorised according to National Institute for Health and Care Excellence (NICE) guidance on referral for suspected cancer. We used linear regression to estimate the mean difference in primary-care interval by cancer, after adjustment for age, gender, and the symptomatic presentation category. RESULTS: Primary-care investigations were undertaken in 3198/5036 (64%) of cases. The median primary-care interval was 16 days (IQR 5–45) for patients undergoing investigation and 0 days (IQR 0–10) for those not investigated. Among patients whose symptoms mandated urgent referral to secondary care according to NICE guidelines, between 37% (oesophagus) and 75% (pancreas) were first investigated in primary care. In multivariable linear regression analyses stratified by cancer site, adjustment for age, sex, and NICE referral category explained little of the observed prolongation associated with investigation. INTERPRETATION: For six specified cancers, investigation in primary care was associated with later referral for specialist assessment. This effect was independent of the nature of symptoms. Some patients for whom urgent referral is mandated by NICE guidance are nevertheless investigated before referral. Reducing the intervals between test order, test performance, and reporting can help reduce the prolongation of primary-care intervals associated with investigation use. Alternative models of assessment should be considered.